Soldier's son - McClelland, Ben W., 1943- (University Press of Mississippi, 2004)
In December 1944 First Lieutenant Ewing R. "Pete" McClelland was captured in the Battle of the Bulge. Soon afterwards in an Allied air attack on the German POW camp where he was held, he was killed. Back home in Pennsylvania, his young widow and three small children survived him. Too young to have lasting recollections, Ben W. McClelland, the soldier's son who was just beyond infancy, became one of the war's fatherless innocents for whom the memories of others would form the paternal image. As the boy evolved into manhood, he reflected on how strange it was to gro.